Influence of NaBH4 on the sensitivity of As3+ and As5+ sensor using gold modified boron doped diamond electrodes - Yuliandri, Pratiwi; Lestarini, Dian Tri; Khalil, Munawar; Einaga, Yasuaki; Jiwanti, Prastika Krisma (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Arsenic is known as one of the carcinogenic metalloids and can cause various health issues when ingested or inhaled over prolonged periods of time. Methods: In this work, boron-doped diamond (BDD) electrode was altered with gold particles (Au) arranged by seeding continued with electrodeposition of HAuCl4 solutions at the electrode surface, will be used as electrode to detect As3+ and As5+ in lake water. The deposited gold particles on the BDD surface were studied with scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) and X-ray photoelectron spectroscopy (XPS). Detections of As3+, As5+, and mixture solutions of As3+ and As5+, carried out with anodic stripping voltammetry (ASV). Findings: The, pre-treatment using NaBH4 carried out for reduction from As5+ to As3+, indicate an improvement at the sensitivity of As3+ and As5+ detection with a good linear responses for each solution in range concentrations of 0.02-0.2 ppm for As3+ and As5+, with R2=0.9759 and R2= 0.9876, respectively. Conclusion: Furthermore, limit of detections of 0.0335 ppm and 0.0239 ppm can be attained for As3+ and As5+ displayed high linearity, revealing that detection of each species of As3+ and As5+ can be conducted in mixture of As3+ and As5+. Novelty/Originality of this Study: This study involves the modification of BDD electrodes with gold (Au) using a combined seeding and electrodeposition technique, which enhances stability and sensitivity for detecting arsenic (As³⁺ and As⁵⁺) at low concentrations. Additionally, the research introduces a pretreatment method using NaBH₄ to facilitate the detection of As⁵⁺ by reducing it to As³⁺, thereby improving the detection limits with anodic stripping voltammetry (ASV).